Computational grids in evolutionary optimization of structures - Kuś, Wacław (Computer Assisted Methods in Engineering and Science, 2005)
The paper is devoted to computational grids applications in evolutionary optimization of structures. The two grid middleware are used, UNICORE and LCG2. The distributed evolutionary algorithm is used for optimizataion. The fitness function is computed using finite element method. Numerical examples are presented.